Utopias can be real. Organisational structures within eco-anarchist communities - Schlüter, Anni (2023)
The climate and biodiversity crisis are some of the most pressing problems (Diaz et al., 2019) caused by anthropogenic actions and the prevalent economic system of capitalism (Li, 2016). Since the current system and societal organisation are additionally contributing to social issues such as growing inequality, other forms of organisational structures and alternative forms of society can offer valuable learning opportunities for the realisation of social utopias. There are many political ideologies that would offer an alternative to capitalism with one of them being anarchism. Anarchism can be understood as a response to the hierarchy and domination in our current society. Forest occupations are organised in an anarchist manner and built on solidarity and voluntary action. These communities do not only exert pressure on the prevailing system, but their organisational structure also impacts individuals and their social interactions. There is lack of research on contemporary lived experiences of anarchism (Williams, 2018) which shows the need for further exploration. This work analyses the organisational structures of eco-anarchist communities by studying forest occupations predominantly located in Germany. To do so, foremost participant observation within the different occupations was applied, complimented by extensive interviews. The main findings show that the organisational structure of the studied occupations results in an individually perceived higher happiness and sense of fulfilment. The anarchist organisation continuously deconstructs the hierarchisation and commodification of humans, values, objects etc. that are usually naturally occurring. To analyse and contextualise these findings, a political ecology framework complemented with power relations theory is applied.